Silicon photovoltaic modules at end-of-life: Removal of polymeric layers and separation of materials. (15th March 2019) - Fiandra, Valeria; Sannino, Lucio; Andreozzi, Concetta; Corcelli, Fabiana; Graditi, Giorgio
Highlights: An efficient management of photovoltaic waste allows the recovery of valuable materials. A new environmentally sustainable two-step process allows the polymers to be removed. A first mechanical step and a thermal second one completely eliminate the polymers. Low emissions assure a good trade-off between technical and environmental targets. Hydrofluoric acid and fluorinated by-products from Tedlar burning aren't formed. Abstract: An eco-friendly process to recover valuable materials deriving from silicon based photovoltaic panels at end-of-life has been proposed. In particular, in this paper a new two-step process to separate and recover glass, Si and metals has been investigated and discussed. A preliminary mechanical treatment to remove fluorinated polymers allows to exclude dangerous emissions of hydrofluoric acid and fluorinated compounds coming out from conventional heat treatments. A subsequent thermal treatment allows the complete removal of the residual polymers and the separation of valuable materials. The influence of treatment time, temperature and atmosphere, during the polymers degradation has been evaluated and the by-products have been examined. The process efficiency has been assessed by determining the quantity and quality of the recovered materials. The results have shown that the combination of the two mechanical/thermal processes allows energy efficiency and environmental sustainability with respect to conventional recovery treatments. The optimal operating conditions for the thermal treatment have turned out 500 °C for 1 h in oxidizing atmosphere. The quality of the recovered materials has been determined by analysing the residual carbon content after the thermal treatment. The gaseous products of the polymeric degradation have been characterized by gas chromatography-mass spectrometry (GC–MS) analysis.